Socio-Educational Factors to Promote Educational Inclusion in Higher Education. A Question of Student Achievement - Mª del Mar García-Vita; Marta Medina-García; Giselle Paola Polo Amashta; Lina Higueras-Rodríguez (Education Sciences, 2021)
Psychosocial factors have a direct impact on the academic achievement of university students, especially when they belong to diverse human groups. This article shows the results of a project developed in a Colombian university with the aim of finding out the identity traits, situations of discrimination, and risk factors faced by students belonging to diverse groups. The research is qualitative, exploratory, and descriptive, approached from a social and educational perspective. Semi-structured interviews were conducted with 15 students. The high level of identification with the group is visible in stufuigureents with affective-sexual diversity, gender identity and ethnic-cultural diversity, considered to be the most discriminated-against populations. Risks in the labor, educational, social, and family spheres are the most frequent.